The Analysis of Liquidity Ratio as Tool to Measure Financial Position in PT. Iplug Indonesia at Medan - Stefvy; Deva Djohan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
The objective of this research study is to know the financial position of PT. Iplug Indonesia, whether if the company can cover up their short term liabilities or not and if they can, how good they can in covering up their short term liabilities. In doing the research, the writer obtains the data from PT. Iplug Indonesia. The writer analyzes the data using descriptive method. Based on data collected, the writer calculated the liquidity ratio to know whether this company can cover up their short term liabilities or not. The writer calculated the liquidity ratio using three methods which is quick ratio, current ratio, and operating cash flow ratio from 2010 until 2014 in other to know can this company cover up their short term liabilities and how good they cover their short term liabilities. Based on data analysis, research data shows that the company has result of 1.05-1.33 in the 2010-2011 and decrease in year 2013-2014 with result of 1.16-1.02, shows that the company current assets is grow faster than their current liabilities while their current liabilities grow faster than their cash flow from operating. This thing makes the quick ratio and current ratio increased while operating cash flow ratio is decreased. Based on data research and analysis, the writer can conclude that the company can cover up their short term liabilities and they are consider good at covering their short term liabilities. But their must more focus on their cash flow from operating because if we look from operating cash flow ratio, it decreasing year by year and it will be not good for the company.